ChatGPT in English Language Learning: User Experience and Enjoyment Among Students and Teachers - Putra, I Komang Ardana; Santosa, Made Hery; Indrayani, Luh (Journal of Educational Study, 2025)
This study employs an explanatory mixed method design to investigate the user experience and enjoyment of ChatGPT among 219 grade 12 students and four English teachers at one high school in Bali. Quantitative data were collected using the User Experience Questionnaire (UEQ) and analyzed with the Data Analysis Tool, while qualitative data were gathered through interviews and subjected to thematic analysis. Results reveal that students had generally positive experiences across dimensions such as attractiveness, perspicuity, efficiency, dependability, and novelty but reported neutral stimulation levels, attributed to high technology dependence and limited social interaction. In contrast, teachers reported uniformly positive experiences across all dimensions and demonstrated greater personal and social enjoyment. The findings indicate that user enjoyment significantly influences overall ChatGPT user experience in educational contexts. This study highlights the need to enhance engagement strategies to improve stimulation for student users, offering important insights for AI integration in education.